Исследование токопроводящих структур вихретоковым методом - Горкунов, Борис Митрофанович; Тюпа, И. В.; Тищенко, Анна Анатольевна (НТУ "ХПИ", 2011)
Приведены результаты исследования материалов, представляющих собой набор трубок и стержней для имитации образца с упрочненным слоем. Построены зависимости выходных сигналов вихретокового преобразователя от сырого и упрочненного образцов.

Researches of materials represented by a set of tubes and rods for modelling of sample with the strengthened layer are resulted. Characteristics of output signals from the eddy-current transformer are got up for normal and strengthened samples.
Researches of layered current-carrying structures by eddy-current method
Keywords: вихретоковый преобразователь; трубки; стержни; material; structure; strengthened layer; electromagnetic characteristics